Are All Mental Disorders Affective Disorders? - Maiese, Michelle (Passion: Journal of the European Philosophical Society for the Study of Emotions, 2023)
A growing number of theorists have looked to the enactivist approach in philosophy of mind or the affordance-based approach from ecological psychology to make sense of a wide variety of phenomena; some theorists believe that these theoretical accounts can offer rich insights about the nature of mental disorders, their etiology, and their characteristic symptoms. I argue that theorists who adopt such approaches also should embrace the further claim that all mental disorders are affective disorders. First, enactivist accounts of mental disorder push us toward such a view insofar as they characterize such conditions in terms of disordered sense-making and conceptualize sense-making as fundamentally affective. Second, conceptions of mental disorder that emphasize affordance perception likewise motivate such a view insofar as they highlight the role that affectivity plays in the disclosure of action possibilities. What is more, both sense-making and affordance disclosure are best understood as processes of selective attention and responsiveness that rely heavily on affectivity. To illustrate and support these claims, I discuss how (a) language disturbances in schizophrenia and (b) “context blindness” in autism both result from disruptions to affectivity and selective attention that make it difficult for subjects to engage effectively with relevant affordances.